PENGARUH TEKNIK RELAKSASI EFFLEURAGE TERHADAP NYERI PERSALINAN KALA I PADA IBU INPARTU DI BIDAN PRAKTEK ZULAINI KOTA LANGSA - Ayunin Syahida (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2022)
Labor pain occurs due to the cervical dilatation process, as the intensity and frequency of the uterus increase, the pain felt will be stronger and peak in the first stage of the active phase, namely the opening of the uterus to 4-10 cm during labor. The Effleurage massage technique is a massage technique in the form of a light massage using the fingers, performed on the abdomen, in rhythm with breathing during contraction. Massage effleurage helps reduce labor pain through the three hierarchical myelinated vagus/parasympathetic autonomic nerves, sympathetic nerves, vagus/unmyelinated parasympathetic nerves. This research method is a quasi-experimental study with a one group pretest-posttest approach by measuring the intensity of pain before and after the intervention. This research was conducted at the practice midwife Zulaini Langsa City using purposive sampling technique. The sample in this study were 16 people. Data analysis was carried out univariately (descriptively) to see the research variables both independent and dependent in the form of frequency distribution and bivariate using the Paired T-Test test to see the effect of the independent variable with the dependent. The first stage of labor pain is known to have a p value (sig) (0.000) < 0.05, which means that there is an effect of the Effleurage Relaxation Technique on the first stage of labor pain in the mother. The average score of labor pain before being given the Effleurage massage intervention was 2.38 and after the Effleurage massage intervention was given the average score for menstrual pain decreased to 1.38. This shows that Effleurage massage is effective in reducing labor pain in the first stage of labor. The conclusion is that there is an effect of the Effleurage Relaxation Technique on the First Stage of Labor Pain in the mother.